Perceptions of Fairness of Support Between Older Parents and Adult Children - Anna Willems; Dimitri Mortelmans; Anina Vercruyssen (Social Sciences)
Increased life expectancy and reduced fertility mean more generations are living simultaneously but with fewer members. There is also a growing group of older people (aged 80 and over) who need care and support. This impacts mutual support within families and the care provided by public or private care organisations. Across OECD countries, on average, 60% of people aged 65 years and older in 2020 reported receiving support from family members, friends and people in their social network, living inside or outside their household but not care organisations. European research shows that when older persons do not have a partner (anymore), they rely on their adult children for care and support. Given that adult children frequently serve as primary providers of informal care, our study examines their perspectives and motivations to provide future care alongside the demands and expectations of their old parents. Our study adopts a multi-actor interview approach and simultaneously looks at the perspective of 40 adult children and one of their older aged parents (65 years or older). We apply the distributive justice theory to understand how children and parents assess the expectation and fairness of support. This paper contributes to the existing literature about support behaviour between parents and children, expanding insights about the fairness of support, expectations and willingness from a multi-actor approach. Through the lens of child–parent dyads, it is seen that the principles of the distributive justice theory can be perceived as not so strict, and within family relationships, one or more principles can coexist and have underlying mechanisms. This study shows the complexity and often ambivalence of family solidarity by adopting a multi-actor approach. One of the main findings is that contrasting dyads who reject the reciprocal act of support experience feelings of guilt or misunderstanding, resulting in stress and worry. A child may not follow the expected support pattern from the parent due to competing demands such as work or the prioritisation of young children, which can reduce the support given to the older parent. Besides general contrasts and similarities between child–parent support perspectives, the analysis looked into differences regarding gender and legal relationships. Our findings only found gendered care expectations. Future research should entangle this by looking into feelings of closeness, emotional connection and considering the dynamic character of filial support over time, especially between siblings.